Growth in milk consumption and reductions in child stunting: Historical evidence from cross-country panel data - Haile, Beliyou; Headey, Derek D. (Elsevier, 2023)
Agricultural and food policies are increasingly being tasked with doing more to improve the nutritional status of low-income populations, especially reductions in child stunting. Which specific food sectors warrant additional policy attention is less clear, although a growing body of research argues that increased animal-sourced food consumption in general, and increased dairy consumption specifically, can significantly reduce the risks of stunting, as well as deficiencies in micronutrients and high quality protein. However, experimental research on dairy’s impacts on child growth in developing countries is very limited, and non-experimental evidence is confined to cross-sectional surveys. In this study we adopt a more macro lens by using a cross-country panel to show that increases in milk consumption over time are associated with large reductions in child stunting even after controlling for important confounding factors. Countries with high rates of stunting should therefore consider nutrition-sensitive strategies to increase dairy consumption among young children through both supply- and demand-side interventions.